Artech 2012. Crossing digital boundaries: proceedings of the 6th International Conference on Digital Arts - Chambel, Teresa (2013)
Atas da "6th International Conference on Digital Arts - crossing digital boundaries", realizada na Universidade do Algarve, Faro, de 7-9 novembro de 2012